Virtual Marriage Contracts and the Shariah Concept of 'Ittihad Al-Majlis': a Case Study of Online Unregistered Marriage Services in Indonesia - Nasiri Nasiri (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2021)
The digitalization of religious rituals has reached a critical juncture with the emergence of online unregistered marriage services (nikah siri online) in Indonesia. This phenomenon challenges the classical Shafi’i doctrine of Ittihad al-Majlis (unity of the session), which traditionally requires physical co-presence. This research aims to analyze the legal validity and teleological implications of virtual marriage contracts within the framework of Usul al-Fiqh and Maqashid al-Shari’ah. Employing a qualitative normative-juridical methodology, the study evaluates classical jurisprudence alongside Indonesian marriage laws and digital ethnography of online service providers. The findings reveal that while modern telecommunications can satisfy the ‘illah (legal cause) of Ittihad al-Majlis through real-time audio-visual synchronization, the practice of virtual marriage in Indonesia remains fundamentally flawed due to its unregistered status. From a Maqashidi perspective, these unions create a systemic mafsadah (harm), including the loss of civil rights for women and children, which outweighs the perceived benefit of avoiding moral transgression. The study concludes that for a virtual "session" to be legally and theologically valid, it must be integrated into a formal-digital state registry. This research provides a framework for reinterpreting "presence" in Islamic law while maintaining the protective essence of the marital covenant.